2001
DOI: 10.1074/jbc.m007674200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Enzymatic Characterization of Two Diverging Murine Counterparts of Human Interstitial Collagenase (MMP-1) Expressed at Sites of Embryo Implantation

Abstract: Remodeling of fibrillar collagen in mouse tissues has been widely attributed to the activity of collagenase-3 (matrix metalloproteinase-13 (MMP-13)), the main collagenase identified in this species. This proposal has been largely based on the repeatedly unproductive attempts to detect the presence in murine tissues of interstitial collagenase (MMP-1), a major collagenase in many species, including humans. In this work, we have performed an extensive screening of murine genomic and cDNA libraries using as probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
172
3
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(182 citation statements)
references
References 49 publications
5
172
3
2
Order By: Relevance
“…Interestingly, this difference was more marked in male than in female mutant mice, indicating the occurrence of a gender difference that has been previously reported in other models of Mmp deficiency (24). The different susceptibility of male and female Mmp1a Ϫ/Ϫ mice to tumor development is likely due to hormonal factors as previously demonstrated in the Mmp8-null model, in which ovariectomy or estrogen receptor antagonist treatment increases the incidence of chemically induced tumors in Mmp8 Ϫ/Ϫ female mice, and abrogates the gender differences in cancer susceptibility (22). Similar studies in Mmp1a-null mice will be necessary to confirm the hormonal basis of the gender differences in cancer susceptibility in these mutant animals.…”
Section: Journal Of Biological Chemistry 14653mentioning
confidence: 50%
See 2 more Smart Citations
“…Interestingly, this difference was more marked in male than in female mutant mice, indicating the occurrence of a gender difference that has been previously reported in other models of Mmp deficiency (24). The different susceptibility of male and female Mmp1a Ϫ/Ϫ mice to tumor development is likely due to hormonal factors as previously demonstrated in the Mmp8-null model, in which ovariectomy or estrogen receptor antagonist treatment increases the incidence of chemically induced tumors in Mmp8 Ϫ/Ϫ female mice, and abrogates the gender differences in cancer susceptibility (22). Similar studies in Mmp1a-null mice will be necessary to confirm the hormonal basis of the gender differences in cancer susceptibility in these mutant animals.…”
Section: Journal Of Biological Chemistry 14653mentioning
confidence: 50%
“…One possibility to explain this lack of functional information about MMP-1 in cancer is the absence of an in vivo model of MMP-1 deficiency, an aspect that has been largely attributed to the wide assumption that no MMP-1 ortholog was present in rodents. However, our finding of two murine genes (Mmp1a and Mmp1b, also known as McolA and McolB) similar to human MMP-1 opened a series of further studies, which allowed us to conclude that Mmp1a is a bona fide counterpart of human MMP-1 (22). This finding was the starting point of a long term work that has now led us to the generation and analysis of mutant mice deficient in Mmp1a.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mcol-A and -B are likely the murine homologues of MMP-1 (Balbin et al, 2001). Based on its chromosome position and enzymatic activity, Mcol-A is a strong candidate to be the murine orthologue of human MMP-1.…”
mentioning
confidence: 99%
“…Furthermore, MMP-2, MMP-9, and MMP-12 lead to emphysema by degradation of elastin fibers (25,26). Therefore, expression levels of collagens, elastin, and a number of MMPs of putative relevance in lung pathology, including McolB (a mouse orthologue of human MMP-1) (27) and MMP-2, -8, -9, -12, -13, and -14, were examined in the lungs of Fut8-mutant mice. RT-PCR analysis showed that there were no significant changes in the expression levels of collagens, MMP-2, -8, and -14 in lung tissues from Fut8 Ϫ/Ϫ , Fut8 ϩ/Ϫ , and Fut8 ϩ/ϩ mice (Fig.…”
Section: Enhanced Expression Levels Of Mmps In Fut8 ؊/؊ Lungs and Futmentioning
confidence: 99%